Outcomes of Left Main Coronary Artery Revascularization after Percutaneous Coronary Intervention or Coronary Artery Bypass Grafting Surgery - Qazi Najeeb Ullah Amin, Irfan Ali Khan, Kashif Ullah Shah, Zia Ur Rehman, Farman Ullah, Sami Ullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Our study's major goal is to examine how several existing ULMCAD Currently, percutaneous coronary intervention (PCI) and coronary artery bypass grafting are the most common non-invasive methods of treating (unprotected left predominant) CAD in the United States (CABG). Place of study and duration: Conducted at the department of Cardiology, Hayatabad Medical Complex, Peshawar for the Duration from July 1 -2016 to Jun 30 -2017. Methods and Results: The effects of PCI and CABG have been analyzed in 558 patients with ULMCAD in a row (suggest age 71.9 years, eighty-one percent male). The most important end results were a total prevalence of mortality, nonfatal MI, and stroke. Diabetes prevalence increased to 29 percent, whereas acute coronary syndrome increased to 56 percent and 11 became the standard Euro SCORE. An extremely complicated form of coronary disease affected 50% of the patients (SYNTAX score >32). Up to four years after PCI and CABG, the primary composite outcomes were equivalent (15, 53, 1 percent vs. 17,126.6 percent; p=0.585). Additionally, the impacts on the top findings were equivalent for the 2 cohorts with similar propensity ratings. Revascularization was required in 5.5 percent of PCI patients and 1.5 percent of CABG patients, respectively, due to ischemia (p=0.010). Conclusions: According to our local network of ULMCAD patients, the long-term scientific outcomes of the present PCI or CABG revascularization procedures were equivalent. No matter the intricacy of the coronary artery.